Pemakaian Eye Mask dan Earplug Terhadap Kualitas Tidur Pasien Pra Operasi Laparatomi - Anita, Anita; Purwati, Purwati; Agustanti, Dwi (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT The prevalence of sleep disorders in the general population is estimated at 15-35% (Kumari S, 2017). Sleep disturbances in inpatient rooms are caused by many factors including environmental factors such as reduced sleep intensity due to the influence of lighting, noise, temperature and the activities of room nurses. Noise and bright light can cause psychological and physiological disturbances. The purpose of this study was to determine the effect of eye masks and ear plugs on sleep quality in preoperative laparotomy patients. This type of quantitative research with quasi-experimental methods. The population in this study were preoperative laparotomy patients, a sample of 60 respondents, the sampling technique was purposive sampling. Analysis with the T test. The results for the pre-intervention-post-intervention group were obtained, namely an average of 0.60 with a standard deviation of 498, and in the pre-control-post-control group, the results were obtained with an average value of 0.13, a standard deviation of 343 with a p-value of 0.000. The results showed that the average value before the intervention was (1.30) with a standard deviation of 466 and after the intervention there was a change in the average value (1.90), a standard deviation of 305. Obtained a p-value of 0.000 (p <0.05), it can be concluded that there is an effect of giving eye masks and ear plugs to the need to fulfill sleep rest in postoperative laparotomy patients in the surgical inpatient room of Dr. Hi. Abdul Moeloek Lampung Province in 2022. Keywords: Eye Mask, Ear Plug, Sleep Quality  ABSTRAK Prevalensi gangguan tidur pada populasi umum diperkirakan 15-35% (Kumari S, 2017). Gangguan tidur di ruang rawat inap di sebabkan banyak faktor di antaranya faktor lingkungan seperti intensitas tidur yang berkurang karena pengaruh pencahayaan, kebisingan, suhu dan aktifitas perawat ruangan, Kebisingan dan cahaya terang dapat mengakibatkan gangguan psikologis dan fisiologis. Tujuan penelitian ini untuk mengetahui pengaruh eye mask, dan ear plugs terhadap kualitas tidur pada pasien pra operasi laparatomi. Jenis penelitian kuantitatif dengan metode quasi eksperimen. Populasi dalam penelitian ini adalah pasien pre operasi laparatomi, sampel sejumlah 60 responden, teknik pengambilan sampling adalah purposive sampling. Analisis data dengan uji t test. Hasil nilai kelompok pre intervensi-post intervensi di dapatkan yaitu rata rata 0.60 dengan standar deviasi 498, dan pada kelompok pre control-post control di dapatkan hasil dengan nilai rata rata 0.13, standar deviasi 343 dengan p-value 0,000. Hasil penelitian didapatkan nilai rata-rata sebelum intervensi yaitu (1,30) dengan standard deviasi 466 dan setelah dilakukan intervensi ada perubahan pada nilai rata-rata (1,90), standar deviasi 305. Didapatkan nilai p-value 0.000 (p<0,05), maka dapat disimpulkan bahwa ada pengaruh pemberian eye mask dan ear plugs terhadap kebutuhan pemenuhan istirahat tidur pada pasien post operasi laparatomi di ruang rawat inap bedah Bedah RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung Tahun 2022. Kata Kunci: Eye Mask, Ear Plug, Kualitas Tidur